2017
DOI: 10.1002/qua.25349
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent dyes in the context of DNA‐binding: The case of Thioflavin T

Abstract: Thioflavin T (ThT) is a dye characterized by a strong fluorescence light‐up on binding to biosubstrates. Although this effect is known to be related to the inhibition of intramolecular torsion on excitation, the binding modes and their role in affecting photoinduced processes are by no means adequately understood. Here, a combined molecular dynamics and quantum chemical modeling is used to study the tuning of the photophysical properties of ThT when moving from solution to DNA binding. The binding mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Interaction of small molecules with dsDNA is usually governed through noncovalent intercalation and groove binding phenomenon . Recent studies have recognized the dominance of hydrophobic forces involved in the interaction between DNA and ThT at lower concentrations of ThT through intercalation binding mode. , Thus, we resorted to a competitive binding study using ethidium bromide, EtBr (a very established DNA intercalator). Addition of different concentrations of ThT to the AT DNA bound EtBr solutions (under saturated conditions of DNA bound to EtBr) resulted in a distinct decrease in the fluorescence intensity of the solution (Figure S8).…”
mentioning
confidence: 99%
“…Interaction of small molecules with dsDNA is usually governed through noncovalent intercalation and groove binding phenomenon . Recent studies have recognized the dominance of hydrophobic forces involved in the interaction between DNA and ThT at lower concentrations of ThT through intercalation binding mode. , Thus, we resorted to a competitive binding study using ethidium bromide, EtBr (a very established DNA intercalator). Addition of different concentrations of ThT to the AT DNA bound EtBr solutions (under saturated conditions of DNA bound to EtBr) resulted in a distinct decrease in the fluorescence intensity of the solution (Figure S8).…”
mentioning
confidence: 99%
“…Recently, interactions of ThT with DNA have been reported. It was found that ThT exhibits a moderate emission enhancement in the presence of single- and double-stranded DNA, whereas a strong fluorescence could be detected upon ThT insertion into DNA cavities such as internal gaps or mismatch sites . Among the specific DNA cavities there are a few of high biological significance, including i-motifs and G-quadruplexes (G4). , Both DNA structures are formed by stacking of Hoogsteen base pairs of cytosines or guanines, respectively.…”
mentioning
confidence: 99%
“…Furthermore,t wo essentially isoenergetic enantiomeric forms (rotamers) of ThT + exist, but their computed S 0 !S 1 transitions are indistinguishable at the B3LYP/6-31 + G(d,p) level, indicating that these conformations are not the sourceo ft he spectralf eaturess paced by % 2000 cm À1 .F inally,m ultiple reports have emerged recently in which computations and ultrafast spectroscopy also point to the spectral importance in various solvents of an additional, short-lived excited electronic state of ThT + ,a lthought here is some disagreement as to the nature of that state. [32][33][34] Our gas-phase results mayi ndicate that this additional state is longer-lived when solvent interactions are removed,and that it is emissive. Thus, we speculate that changes in relative transi-tion intensities between these electronically accessible transitions may underlie the sensitivity of the absorption spectra of ThT to its molecular environment.…”
mentioning
confidence: 83%